Sorption properties of materials based on polyvinylpyrrolidone copolymers - Levytskyy, Volodymyr; Khromyak, Ulyana; Suberlyak, Oleh (Publishing House of Lviv Polytechnic National University, 2010)
Sorption properties of polyvinylpyrrolidone copolymers regarding to different acid-base indicators, as well as heparin and iodine have been investigated. The amount of sorption active centers of synthesized copolymers depends upon synthesis conditions, namely upon temperature and initiator amount, and is determined by the nature of sorbates and copolymers functional groups. Досліджено сорбційну здатність кополімерів полівінілпіролідону відносно різноманітних кислотно-основних індикаторів, а також гепарину та йоду. Встановлено, що кількість активних центрів сорбції синтезованих кополімерів залежить від умов синтезу, а саме температури процесу та кількості ініціатора, і визначається природою функціональних груп сорбованих речовин та кополімеру.
Сорбіційні властивості матеріалів на основі кополімерів полівінілпіролідону
Keywords: copolymers; polyvinylpyrrolidone; sorption; indictors; polystyrene; polymethylmethacrylate; кополімери; полівінілпіролідон; сорбція; індикатори; полістирол; поліметилметакрилат